Building Capacity of Occupational Therapy Students to Address the Mental Health Needs of Children and Youth during a Level II Fieldwork in a School Setting. Issue 4 (1st October 2020) - Bazyk, Susan; Pataki, Kristen; DeBoth, Kelle
ABSTRACT: To explore the meaning and outcomes of a virtual building capacity process designed to promote knowledge translation of a public health approach to mental health with children and youth by occupational therapy students completing a Level II Fieldwork experience in school settings. A one-group ( n = 19) mixed design using quantitative (pretest-posttest survey) and qualitative methods (phenomenological analysis of written reflections) was used to explore the meaning and outcomes of participation in the virtual building capacity process . Statistically significant improvements ( p <.00) in pretest-posttest scores of knowledge, beliefs and actions related to addressing mental health were found in 7 of the 9 categories. Four qualitative themes emerged from the data: New thinking regarding 'mental health'; Gearing up for change; Planning led to implementation; and the Building capacity process was meaningful and enjoyable. The building capacity process expanded student knowledge of a public health approach to mental health resulting in increased awareness and application of embedded strategies to address the mental health needs of students during a Level II Fieldwork experience in school settings.